The Global Community yearbook of international law and jurisprudence 2015 - Ziccardi Capaldo, Giuliana; Global Community (New York, NY : Oxford University Press, 2016)
The 2015 edition of 'The Global Community Yearbook of International Law and Jurisprudence' constitutes the only thorough annual survey of major developments in international courts. General editor Giuliana Ziccardi Capaldo selects excerpts from important court opinions as well as the contributors who provide expert guidance on those cases.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 28, 2016).
Keywords: International law -- Periodicals; Jurisprudence -- Periodicals; Law; International law